The modulation over time of the effets of its decisions by the French Counsil of State: the search of a balance between legality and certainty - Mathieu, Ninon (Journal of the Belarusian State University. Law, 2020)
Traditionally the annulment of an administrative act by the Council of State, the highest administrative court in France, has a retroactive effect: the act is considered as having never existed. This construction is consistent with the requirements of the principle of legality, aimed to guarantee the overall coherence of the legal system. On the other hand, it might conflict with the need of stability of legal relations, and thus raise a problem of legal certainty. In 2004, the Council of State acknowledged for the first time its own power to modulate the temporal effects of its decisions. Since then, the administrative courts decide on a case-by-case basis how their decisions take effect over time. This article first purposes to present the case-law developments in this area, in order to then discuss the implications of this principle of legal certainty over the court’s jurisdiction and the nature of the litigation.
Keywords: French law; administrative law; case law; legal certainty; principle of legality; legal effects over time